Korelasi Kemampuan Membaca Al-Qur’an Dengan Hasil Belajar Al-Qur’an Hadis Siswa Kelas VIII Di MTsN 7 Agam - Riri Harmanida; Supriadi Supriadi; Jasmienti Jasmienti; Darul Ilmi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research is motivated by a number of problems that the authors found in class VIII MTsN 7 AGAM, especially in the Al-Qur'an Hadith subject. which is mediocre, while students who have poor ability to read the Qur'an obtain satisfactory learning outcomes. This research is a correlational quantitative research. The population in this study was that the researchers did not take all of the students, but the researchers took only class VIII, VIII, and IX. The sample in this study consisted of 56 students. Based on the results of the analysis and discussion of the research data, the results of hypothesis testing are obtained using a simple linear regression formula, so the parametric statistical test results can be seen if sig (2-tailed = 0.001 ≤ 0.025 then H is rejected and H is accepted. Correlation coefficient 0.426 is included in the moderate correlation because it is in the range of 0.400-0.599.So it can be concluded that there is a relationship/correlation between the ability to read the Qur'an and the learning outcomes of Al-Qur'an Hadith for class VIII students at MTsN 7 AGAM.